Enhanced wavelength-sensitivity of volume holographic grating with dual-photoinitiation system in polymer-dispersed liquid crystal. Issue 4 (16th March 2019) - Wang, Kangni; Zheng, Jihong; Qian, Linyong; Liu, Yourong
ABSTRACT: We propose a method to improve the wavelength-sensitivity of a volume holographic grating by mixing dual-photoinitiation dopants, namely, rose bengal (RB)/N-phenylglycine (NPG) system and methylene blue (MB)/ p -toluenesulfonic acid (PTSA) system, which enable the fabrication of gratings upon both green and red light illumination. The RB/NPG green light photoinitiation system is chosen in combination with the red-active MB/PTSA system because RB and MB absorb light near 567 and 665 nm independently. In this case, the holographic gratings, recorded in polymer-dispersed liquid crystal, can be fabricated simultaneously by two different visible laser lights with an output wavelength of 532 and 632.8 nm. The electro-optical performances of the gratings exposed upon 532 and 632.8 nm have been implemented: the diffraction efficiencies (DE) are 75% and 57% respectively when the exposure time is optimised to 2 min and 17 min; the threshold voltage is approximately 2.9 V/μm. The enhanced wavelength-sensitivity of holographic gratings allows for the storage of three-dimensional (3D) images on the same hologram plate, and these 3D images are easily reconstructed by both red and green light. Graphical Abstract: